Perioperative immune checkpoint inhibitors plus chemotherapy versus chemotherapy alone in resectable gastric and gastroesophageal junction adenocarcinoma: a systematic review and meta-analysis - Din, Hyder Mohammad Waseem; Gurram, Yamini Saraswathi; Mansur, Aimen; Shahid, Mohammad Maroof; Saleem, Tayyaba Binte; Kumari, Karoona; Kumar, Beesham; Kumar, Pershan; Shahid, Maira; Abdurrahman, Mahmud Seyi; Khawar, Muneeb (Nepal Journal of Epidemiology, 2026)
Background: Gastric and gastroesophageal junction (GEJ) cancer is not responsive to surgery and perioperative chemotherapy. Immune checkpoint inhibitors (ICIs) have been effective in advanced disease. This meta-analysis assesses the benefits of the addition of ICIs to perioperative chemotherapy in case of resectable gastric/GEJ cancer.Methods: PubMed, Embase, Cochrane CENTRAL and Web of Science were identified until 2026. Randomized controlled trials with comparison of perioperative ICI with chemotherapy against chemotherapy were included. A random-effects model was used to. Risk ratios was calculated for all the dichotomous outcomes. I² was used to assess the heterogeneity.Results: Four trials (2,125 patients) were included. ICI plus chemotherapy, however, had significant positive effects on pathological complete response (RR = 2.87; 95% CI: 1.66 -4.99; p = 0.018) and complete tumour regression (RR = 2.74; 95% CI: 1.24 -6.04; p = 0.006). No significant different was found for R0 resection rates and surgery completion between the two groups. Similarly, no significant different was found for adverse events, surgical morbidity, or deaths. However, immune-related adverse events (RR = 3.18; 95% CI: 2.48–4.08) and treatment discontinuation (RR = 1.31; 95% CI: 1.11–1.54) were significantly higher in ICI plus chemotherapy group.Conclusion: The inclusion of ICIs in perioperative chemotherapy enhances pathological response and does not pose more surgical risk. Although adverse events were high in the ICI plus chemotherapy group so large scale studies are needed to validate these findings.